Enhancing and Development of Human Resources Capabilities for Nuclear Facilities in the Arab Countries Embarking on Nuclear Programs. (Journal of Nuclear Technology in Applied Science, 2018)
To achieve and maintain high levels of safety and security in nuclear facilities, these facilities must be staffed with an adequate number ofhighly qualified and experienced manpower and workforce who are duly aware of the technical and management requirements of safe operation.The main challenge facing countries embarking on nuclear power is to enhance the capacity building and human resources. This paper presents a regional strategic road map to enhance and strengthen human resources capabilities in Arab Countries (ACs) embarking on nuclear power pro-grams, which is the case of United Arab Emirates (UAE), Egypt and Jordan. This strategic road map could be applied by establishing an Integrated Regional Administrative System (IRAS) within the frame-work of the Arab Network for Nuclear Regulators (ANNuR). The main objectives of this system are to activate, support and enhance capacity building and human resources development programs. This system could be administrated under the umbrella and supervision of both AAEA (Arab Atomic Energy Authority) and IAEA. This paper discusses and formulates a framework for the various aspects and structural compo-nents of this system. Egypt regulatory capabilities regarding nuclear andradiological regulatory activities are reviewed. The paper outlines anddiscusses the goals and capabilities of the AAEA and ANNuR regard-ing supporting IRAS objectives. Challenges and needs of ACs regarding nuclear energy utilization are reviewed. Emphasis is focused on Safety and Security (S&S) issues in ACs, and IRAS capabilities and its role for supporting and assisting ACs embarking on nuclear power.
Keywords: Human Resources; Arab Countries; Nuclear Facilities